The Impact of the Code of Ethics on Educators at SMPN 21 Mataram - Yayu Septiana; Datira Hikma Zahra Yustita; Ery Khairia; Cantika Auralia Putri; Yunita Puspitasari; Edy Herianto (al-Afkar, Journal For Islamic Studies, 2026)
The purpose of this research is to analyze the condition of understanding. The condition of understanding and applying the Code of Ethics for Educators towards fellow Educators and students at SMPN 21 MATARAM, where this Code of Ethics is a set of moral principles that serve as guidelines or standards that must be adhered to and practiced by students and fellow Educators. This can affect the relationship between students and educators, educators with fellow educators, and even the social status of educators in the eyes of the community. In our research, we applied a qualitative approach using data collection techniques such as observation, interviews, questionnaires, and documentation with students and educators at SMPN 21 Mataram. The observation results indicate that the understanding and application of the Code of Ethics by students towards educators at SMPN 21 Mataram are already optimal, requiring discipline and mutual respect from educators, and positively impacting the continuity of learning. Educators are expected to be disciplined, respectful, and to uphold the dignity and reputation of the educational institution. Educators who apply the code of ethics can create a comfortable and harmonious learning environment for students and educators. Educators will also be able to understand and implement the code of ethics that fosters relationships and interactions between educators and students, creating a comfortable, facilitative, and harmonious atmosphere at SMPN 21 Mataram.